OC-018 ASSESSMENT OF A SUPPORT GARMENT IN RELATION TO A PARASTOMAL BULGE – A QUALITATIVE STUDY. (13th October 2022) - Krogsgaard, M; Borglit, T B; Theisen, S Z; Rothmann, M J
Abstract: Aim: To investigate patients' experiences of the assessment of support garments in relation to a parastomal bulge. Material and Methods: A qualitative study with 11 in-depth semi-structured interviews. A preceding systematic literature review and a small field study conducted before the study informed the main topics in the interview guide. Results: Garments had to fit patients' needs and personal preferences; being comfortable, flexible and user-friendly. When comorbidities, e.g., incontinence, poor balance, arthritis and visual impairment were not accounted for, garments were unmanageable to patients. Patients needed guidance on how to apply and use the garment. Lack of hands-on guidance left patients confused and helpless with unworn garments. Re-assessment of a garment necessitated several visits to the manufacturer, was time-consuming and stressful for patients and required patients' physical and mental resources. The garment created new possibilities and challenges; well-assessed garments reduced symptoms from the parastomal bulge while poorly assessed worsened or induced new symptoms and ended up unworn. Conclusion: Exploring patients' expectations, symptoms, needs and comorbidity were vital for patients' subsequent use and benefit of garments. Tailor-made information, guidance and professional assistance are important in the assessment process. Interventions to support a patient-centred, individual and systematic approach are warranted.